Mutual Cooperation In The Modern Era: Is It Still Relevant? - Nugraha, Ramdan Eka; Pradiva, Vania Ailla (ann4publisher@gmail.com, 2025)
Background. Gotong royong is a cultural value rooted in the life of the Indonesian people. It reflects the spirit of togetherness, help-to-help, and cooperation in solving various social problems. However, as times develop and lifestyles become increasingly individualistic, these values face challenges in maintaining. Aim. This research aims to analyze the relevance of the culture of mutual cooperation in the modern era and how this culture is still applied despite social changes. Methods. The study used a qualitative approach with in-depth interview techniques with three respondents who lived in the KPAD area. The data obtained was analyzed to identify the form of mutual cooperation implementation and its supporting and inhibiting factors. Results. The study's results show that mutual cooperation is still carried out in various forms, such as community service, social activities, and the construction of public facilities. However, several obstacles, such as individual busyness, differences in values between generations, and the influence of technology, decrease active community participation. Conclusions. The culture of cooperation is still relevant in the modern era, but it requires adjustment to the current context of life to remain effective. Implications. Preservation efforts can be carried out through increasing public awareness through socialization, community coaching, and involving the younger generation in community activities to strengthen the spirit of togetherness. Avoid writing literature citations and abbreviations in the abstract. Don't forget to include the title of the research.